In silico pharmacophore modeling and simulation studies for searching potent antileishmanials targeted against Leishmania donovani nicotinamidase. (December 2019) - Chauhan, Nutan; Poddar, Raju
Graphical abstract: Three point 3D pharmacophore model for Nicotinamidase with ML, Acc and Hyd/Aro features. Highlights: In-silico three-dimensional structure of nicotinamidase was predicted and validated. Three points pharmacophore model including Excluded volume was built and used for database screening. Pharmacophore model validation was performed through MD simulation. Best compound-enzyme complex was proved more stable than another ligand-enzyme complex. Abstract: Nicotinamidase is a key enzyme for the salvage pathway catalyzing the first step for the conversion of nicotinamide (NAm) to nicotinic acid (NA) required for the synthesis of Nicotinamide Adenine Dinucleotide (NAD + ) in the subsequent steps. Leishmania protozoan parasites are NAD + auxotrophs and need precursors (nicotinamide, nicotinic acid, nicotinamide riboside) from their host environment to synthesize NAD + for their survival. Interestingly, absence of this enzyme in higher eukaryotes and its absolute requirement in the developmental cycle of Leishmania has led nicotinamidase an attractive drug target towards leishmaniasis. Hence, we report some potential inhibitors for nicotinamidase screened based on 3-D pharmacophore model consisting of "ML", "Hyd|Aro", "Acc" and "Excl vol" features. Subsequently, dynamics simulation studies validate the proposed pharmacophore model suggesting its reliability for future studies. Furthermore, these essential site-specific features will help in enhancing the inhibition of nicotinamidase activity. Results of our study suggest that blocking of active site of nicotinamidase by the identified lead inhibitor will have major impact on the infectious processes and the survival of the parasite. Furthermore, due to the structural homology in the enzyme among L. donovani, L. infantum, L. major, we anticipate that our study would help to design more potent drug candidates against leshmaniasis for these three species.